Control of Intracellular Francisella tularensis by Different Cell Types and the Role of Nitric Oxide - Sarah L. Newstead; Amanda J. Gates; M. Gillian Hartley; Caroline A. Rowland; E. Diane Williamson; Roman A. Lukaszewski (Journal of Immunology Research)
Reactive nitrogen is critical for the clearance of Francisella tularensis infections. Here we assess the role of nitric oxide in control of intracellular infections in two murine macrophage cell lines of different provenance: the alveolar macrophage cell line, MH-S, and the widely used peritoneal macrophage cell line, J774A.1. Cells were infected with the highly virulent Schu S4 strain or with the avirulent live vaccine strain (LVS) with and without stimuli. Compared to MH-S cells, J774A.1 cells were unresponsive to stimulation and were able to control the intracellular replication of LVS bacteria, but not of Schu S4. In MH-S cells, Schu S4 demonstrated control over cellular NO production. Despite this, MH-S cells stimulated with LPS or LPS and IFN-γ were able to control intracellular Schu S4 numbers. However, only stimulation with LPS induced significant cellular NO production. Combined stimulation with LPS and IFN-γ produced a significant reduction in intracellular bacteria that occurred whether high levels of NO were produced or not, indicating that NO secretion is not the only defensive cellular mechanism operating in virulent Francisella infections. Understanding how F. tularensis interacts with host macrophages will help in the rational design of new and effective therapies.